E-LEARNING THROUGH STUDENT VOICES: AN EXPLORATORY STUDY IN HEALTH SCIENCES EDUCATION - Tsary Rumalessin, Ummu; Vera, Lusi Olis (Komunitas Manajemen Kompetitif, 2025)
The widespread adoption of e-learning in higher education has persisted beyond the COVID-19 pandemic. By capturing the voices of health sciences students, this study aimed at providing a rich and robust understanding of their experiences with online learning. An exploratory study was conducted at University of 'Aisyiyah Yogyakarta using purposive sampling, involving 30 health sciences students from various disciplines, including nursing, anesthesiology, midwifery, physiotherapy, nutrition, medical laboratory technology, and radiology. Data were collected through in-depth semi-structured interviews and analyzed using content analysis to gain a comprehensive understanding of students' perceptions and experiences regarding online learning. This study found that health sciences students generally perceived online learning positively, highlighting its ease of access, flexibility, and enhanced communication as key advantages. Participants noted that the online format facilitated greater engagement and improved their ability to plan and participate in case-based learning activities presented by lecturers. Despite these benefits, students expressed reservations about the complete substitution of face-to-face instruction. They emphasized that, due to the practical and hands-on nature of health sciences education, online learning should serve as a complementary approach rather than a full replacement for traditional in-person learning.